Hipotesis Monitor Stephen Krashen dan Reorientasi Pembelajaran Istima-Kalam - Tulus Musthofa; Chairani Astina; Rifqi Aulia Rahman (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
In this study, Author explains the monitor hypothesis of Stephen Krashen and Istima-Kalam Learning. With the hope of being able to provide solutions to the obstacles that have been experienced by Arabic language teachers and learners, especially when learning Istima-Kalam. The monitor hypothesis in istima-kalam learning must include instructions and correction procedures for each material learned and experienced by students. The correction process also needs to consider the smallest element of Arabic, namely harf. Students with difficulty pronouncing certain letters, must be given instructions or directions and monitored intensely. The instructions and corrections are needed to see to what extent the participants are able to master the correct pronunciation of letters, master the formation of words, and sentences according to tarakib in accordance with ‘ílm sharf (Arabic morphology) and ‘ilm nahw (Arabic syntax). Only then arrange connections and adjustments (muthabaqah) between sentences to become meaningful and acceptable oral or written.